THE PICTURE AND CULTURAL STRUGGLE OF THE BALINESE WOMEN IN THE NOVELS WRITTEN BY PANJI TISNA, PUTU WIJAYA, AND OKA RUSMINI - Artawan, Gde; Kutha Ratna, I Nyoman; Weda Kusuma, I Nyoman; Suarka, I Nyoman (e-Journal of Linguistics; Vol. 5. Januari 2011 No. 2)
This study aims at revealing the picture and cultural struggle of the Balinesewomen in the novels written by Panji Tisna, Putu Wijaya, and Oka Rusmini, identifyingthe intertextuality of their works and the women’s attitude towards sociopoliticaldiscourse and the discourse of equality in gender. The texts investigated are the novelswritten by Panji Tisna entitled Ni Rawit Ceti Penjual Orang (1935) and Sukreni GadisBali (1936); the novel written by Putu Wijaya entitled Putri published in two books(2004); and the novels entitled by Tarian Bumi (2000) and Kenanga (2003).The theories such as the sociological theory of literature, the theory of feminismand the theory of intertextuality were adopted for investigating the novels. The resultsof the study show the real situation undergone by the women such as the strongconfinement of tradition, the manifestation of the situation undergone by themarginalized and subordinated women, suppression, taming (cooptation), the role ashard workers (double-burden), the role as single parents, the victims of violence and thetaming process (cooptation). Based on such a real situation, the female characters in thenovels showed their cultural struggle by accentuating concepts/the framework ofthinking, reinterpreting and behaving towards tradition. From the intertextuality point ofview, the female characters in the novels were consistent in their vision towardstradition. This was shown by implementing ideas/insights, reinterpreting and behavingtowards the space in the texts. However, as far as sociopolitical discourse and thediscourse of equality in gender are concerned, they behaved differently. Somecompromised on sociopolitical reality and equality in gender and the others were highlyreactive and tended to show struggles through their ways of thinking and behaving.This is the only study which has investigated the novels written by Panji Tisna,Putu Wijaya and Oka Rusmini at the same time. The novelty is that there isintertextuality among the novels. Such intertextuality is in the form of thematicelements which include sociopolitical discourse and the discourse of equality in gender.